Gene identification in the obligate fungal pathogen Blumeria graminis by expressed sequence tag analysis - Thomas, S.; Rasmussen, S.; Glaring, M.; Rouster, J.; Christiansen, S.; Oliver, Richard (2001)
Powdery mildew of barley is caused by the obligate fungal pathogen Blumeria graminis f. sp. hordei. Haploid conidia of B. graminis, landing on the barley leaf, germinate to form first a primary germ tube and then an appressorial germ tube. The appressorial germ tube differentiates into a mature appressorium from which direct penetration of host epidermis occurs. Here we present data on 4908 expressed sequence tags obtained from B. graminis conidia. The combined sequences represent 2676 clones describing 1669 individual genes. Comparison with sequences from other pathogenic and nonpathogenic fungi defines hypotheses on the genes required for pathogenicity and growth on the host. The putative roles of some of the identified genes are discussed.